Signaling theories of religion models and explanation - Brusse, Carl (2020)
The signaling theory of religion has many claimed virtues, but these are not necessarily all realizable at the same time. Modeling choices involve trade-offs, and the available options here have not traditionally been well understood. This paper offers an overview of signaling theory relevant to the signaling theory of religion, arguing for a narrow, “core” reading of it. I outline a broad taxonomy of the choices on offer for signaling models, and examples of how previous and potential approaches to modeling religious signaling meet or fail to meet the initial promise of the theory. A pluralist approach to religious signaling seems possible, but this would require a high level of detail and specificity with respect to both formal models and target systems.
Keywords: Religion; Evolution; Explanation; Modeling; Signaling